How to serve faster in tennis: the influence of an altered focus of attention and augmented feedback on service speed in elite players - Keller, M.; Kuhn, Y. A.; Lüthy, F.; Taube, W. (The Journal of Strength and Conditioning Research, 2021)
Different approaches, such as providing augmented feedback (AF) or adopting an external focus of attention (EF), have been shown to directly enhance performance in recreational athletes. Furthermore, research has shown that combining AF with EF (AF + EF) results in superior performance compared to AF and EF alone. Here, we tested the influence of AF, EF, AF + EF, and an internal focus of attention (IF) on service speed in elite tennis players. High-level national tennis players (19.2 ± 3.7 years) were asked to serve flat serves to a target zone with maximum speed. With respect to service speed, a significant main effect of condition was found (p = 0.001). Post hoc comparisons revealed faster serves for AF compared to control serves without instruction/feedback (p < 0.01) and compared to EF (p < 0.05), whereas no significant difference was found between EF and IF (p = 0.81). The fastest service speeds were found in the AF condition, whereas the combination of AF + EF did not further promote performance. The number of serves landed in the target zone did not differ between conditions (p = 0.17). Thus, no speed-accuracy trade-off was found, indicating that enhanced service speeds did not result in less serves landed in the target zone. Augmented feedback seems most beneficial to instantly enhance tennis serve performance. In contrast to previous studies with recreational sportsmen, EF did not differ from IF, providing further evidence that expertise level and task-relevant instructions mediate the influence of attentional focus on motor performance.